2001
DOI: 10.1177/0734242x0101900610
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of industrial wastes reuse as construction materials

Abstract: This study concerns the reuse of two inorganic wastes, foundry residues and fly ashes from municipal solid waste incineration, as "recycled aggregate" in concrete production. This kind of reuse was optimised by waste treatment with the following steps: waste washing with water; waste stabilisation-solidification treatment with inorganic reagents; final grinding of the stabilised waste after curing for about 10-20 days. Both the treated wastes were reused in concrete production with different mix-designs. Concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In the S/S treatment, cement, lime, sodium silicate, bentonite, blast-furnace slag, and water dosage of 30-40% was used, and involves homogenization during 15 min and a curing phase during 15-20 days. The stabilized waste was ground (<1.5 mm) and the concrete is prepared with these aggregates Collivignarelli and Sorlini (2001) Cementitious building materials FA The FA of an incineration process, which previously separates metals, batteries, glass and ceramics were used to produce cementitious building materials. The considered FA exhibits pozzolanic action Gerdes and Wittmann (1994) Blocks and pavement bricks FF + BA Producing permeable blocks and pavement bricks from molten slag made by a surfacemelting furnace.…”
Section: Discussionmentioning
confidence: 99%
“…In the S/S treatment, cement, lime, sodium silicate, bentonite, blast-furnace slag, and water dosage of 30-40% was used, and involves homogenization during 15 min and a curing phase during 15-20 days. The stabilized waste was ground (<1.5 mm) and the concrete is prepared with these aggregates Collivignarelli and Sorlini (2001) Cementitious building materials FA The FA of an incineration process, which previously separates metals, batteries, glass and ceramics were used to produce cementitious building materials. The considered FA exhibits pozzolanic action Gerdes and Wittmann (1994) Blocks and pavement bricks FF + BA Producing permeable blocks and pavement bricks from molten slag made by a surfacemelting furnace.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these chemicals are used at industrial level [8,29]. On other hand, during the treatment, no toxic gases are produced, and the phosphates and silicates of metals are very stable in the environment.…”
Section: Stabilization With Soluble Phosphates and Silicatesmentioning
confidence: 99%
“…In the literature, several studies concerning chemical stabilization of different incineration residues can be found [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], with some works investigating the effect of chemicals in combination with solidification [15,22,25], and soluble phosphates are the mostly tested additives [7][8][9][10][11]14,16,21,26]. However, chelating agents [11,15,17,27], ferrite and/or ferrous sulphate [12,18,19,23], colloidal aluminate oxide [20], sodium sulphide [15] and soluble silicates [22,28,29] have also been used. The stabilization process with soluble phosphates (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Because the space available for landfills is limited, it would be beneficial to utilize waste ash rather than dispose of it. For example, utilizing waste ash in construction materials is considered to be feasible [1]. Fly ash produced by the combustion of coal is beneficial when used as a soil amendment to improve physical properties (such as soil water-holding capacity [2,3]); to improve chemical properties by increasing cation exchange capacity (CEC) [4]; to provide essential elements such as Si, P, K, and B to plants; to adjust soil pH to levels more suitable for agriculture [5].…”
Section: Introductionmentioning
confidence: 99%